Vascular stiffness determined from a nocturnal digital pulse wave signal: association with sleep, sleep-disordered breathing, and hypertension. Issue 12 (December 2016) - Svedmyr, Sven; Zou, Ding; Sommermeyer, Dirk; Ficker, Joachim H.; Randerath, Winfried; Fietze, Ingo; Sanner, Bernd; Hedner, Jan; Grote, Ludger
Abstract : Objectives: Reflection of the finger pulse wave form is a valid measure of arterial stiffness, which may be continuously assessed during sleep. We investigated the relationships between sleep, sleep-disordered breathing, hypertension, and pulse propagation time (PPT) in patients with suspected sleep apnea. Methods: The digital photoplethysmographic signal derived from finger pulse oximetry was recorded during overnight sleep studies in 440 patients (64% men, age 55 ± 12 years, BMI 30 ± 6 kg/m 2, apnea–hypopnea index 19 ± 19 n/h). PPT, defined as the time interval between the systolic and diastolic peak of the finger pulse wave, was calculated. The influence of sleep stages on PPT were assessed in patients undergoing polysomnography. Generalized linear models were used to study predictors of PPT and hypertension. Results: Mean overnight PPT was independently associated with age (β = −1.34, P < 0.001), height (β = 0.47, P = 0.047), history of smoking (β = −9.44, P = 0.005), and apnea–hypopnea index (β = −0.18, P = 0.043). PPT was shorter in hypertensive patients compared with normotensive patients (160 ± 33 vs. 177 ± 47 ms, P < 0.001) and independently associated with a diagnosis of hypertension ( P = 0.043). PPT was influenced by sleep stage (highest PPT during slow wave sleep compared with wake and all other sleep stages, all P < 0.001) and varied across sleep apnea severity groups in normotensive but not in hypertensive patients ( P = 0.028 and 0.64, respectively). Conclusion: Overnight PPT by oximetry was strongly associated with factors known to determine daytime vascular stiffness. In addition, PTT provides information on functional and structural vascular properties during sleep. This novel technique offers new opportunities to noninvasively monitor vascular function during the sleeping period.